Narration of a collective traumatic event according to the presence of PTSD and considering the social function - Charretier, Laura; Eustache, Francis; Laisney, Mickael; Dayan, Jacques; Fraisse, Florence; de La Sayette, Vincent; Gagnepain, Pierre; Chakli, Amine; Klein-Peschanski, Carine; Peschanski, Denis; Quinette, Peggy (Frontiers in Psychiatry, 2024)
IntroductionIndividuals suffering from PTSD recount the traumatic event using perceptual, emotional and sensory details. Memorization and recall of individual events are influenced by the individual’s social function, i.e., what they are willing and able to share about themselves with others and the society. While the influence of PTSD on narratives has been studied, few studies have measured the effect of social function on the link between PTSD and narrative.ObjectivesThe aim was to measure trauma narratives of the terrorist attacks of November 13, 2015, according to the presence of PTSD and considering the social function (civil or professional) at the time of exposure.MethodsThirty-seven civilians (including 16 women and 21 men) and 22 first responders (including 7 women and 15 men) exposed to the terrorist attacks of November 13, 2015, in France recounted their experiences. Textometric analyses were carried out to characterize the narrative lexicons of the 4 groups (civilians with PTSD; civilians without PTSD, first responders with PTSD; first responders without PTSD).ResultsThe narratives of civilians with or without PTSD contain emotional details of the event. The narratives of first responders with and without PTSD contain details of intervention and team. The narratives of civilians and first responders with PTSD contain elements of social and family contacts. The narratives of civilians and first responders without PTSD contains elements of collective control and aid. Civilians with PTSD mostly use the “I” in narratives, while first responders without PTSD mostly use the “we” narrative and the notion of colleague.ConclusionTrauma narratives of individuals exposed to the same collective traumatic event who have developed PTSD are characterized by information about social and family contexts. Trauma narratives of individuals without PTSD show a sense of control and collective support. Associated with PTSD, the social function during the event influences the narrative, involving self-centered statements (first person singular, individual reactions) for exposed civilians, and allo-centered statements (colleagues, victims) for exposed professionals. This study underlines the importance of considering the inclusion of reference to the social group to which one belongs when testifying about peritraumatic experiences to others.